Aurora kinase A inhibition reverses the Warburg effect and elicits unique metabolic vulnerabilities in glioblastoma - Trang T. T. Nguyen; Enyuan Shang; Chang Shu; Sungsoo Kim; Angeliki Mela; Nelson Humala; Aayushi Mahajan; Hee Won Yang; Hasan Orhan Akman; Catarina M. Quinzii; Guoan Zhang; Mike-Andrew Westhoff; et al. (Nature Communications, 2021)
Glioblastoma patients are treated with Aurora kinase A (AURKA) inhibitors but resistance can occur. Here, the authors show that AURKA inhibition induces metabolic reprogramming, which leads to increased mitochondrial activity and inhibition of oxidative metabolism sensitizes glioblastoma cells to AURKA inhibition.